Pembagian Harta Waris Dalam Islam Menurut Masyarakat Suku Bugis Di Kecamatan Kongbeng - Ahmad Nur; Hartono; Siti Munfiatik (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The majority of Bugis people in Kongbeng Subdistrict embrace Islam, but for the distribution of inheritance property it is still unknown what system they use. The purpose of this research is to know and understand how the practice of dividing inheritance property is applied by the Bugis community in Kongbeng District, this research uses descriptive qualitative research methods. The results of this study are: (1) The Bugis tribe community uses the customary inheritance distribution system by deliberation and prioritizes giving houses to daughters. (2) Many people do not understand the distribution of inheritance law according to Islam. (3) Factors that cause them to use the customary system include: (a) The concept of justice in different customary traditions, (b) Avoiding social jealousy in the family, (c) Economic and practical factors, (d) lack of understanding of Islamic inheritance law. (4) Some Bugis communities show dissatisfaction with the distribution of inheritance according to Islamic law. (5) Many Bugis communities distribute inheritance equally.